Upaya Petani Sawit dalam Meningkatkan Pendapatan di Jorong Simpang Tiga Alin Gunung Tuleh - Nurfadilah Nurfadilah; Sandra Dewi (Lembaga Yasin AlSys, 2026)
Efforts to increase the income of oil palm farmers have received attention in several studies, but research that specifically discusses the integration of farmers’ income improvement strategies with the perspective of Islamic Economics in a local context remains limited. This study aims to analyze farmers’ efforts to increase income in Jorong Simpang Tiga Alin, Gunung Tuleh Subdistrict, from the perspective of Islamic Economics. This study employed a qualitative approach with a case study design, involving 20 informants selected through purposive sampling. Data were collected through interviews and observation, and were then analyzed descriptively and qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results showed that oil palm production tended to decline during the 2022–2024 period even though the land area remained relatively constant, while farmers’ income fluctuated from year to year. The efforts made by farmers to increase income included optimizing land use, using superior seedlings, applying intensive fertilization, and implementing simple mechanization. These findings indicate that increasing farmers’ income is determined not only by the efficiency of managing production factors, but also by the application of the values of justice, maslahah, and sustainability in farm management. The conclusion of this study affirms the importance of strengthening production efficiency and access to resources in order to increase farmers’ income, while also providing theoretical implications for the development of Islamic Economics studies and practical implications for the formulation of agricultural policies that are more supportive of farmers’ welfare.